Identity, Citizenship and the Teaching Profession: Theoretical Insights in the Study of Zambian Teachers Living with Human Immune–deficiency Virus (HIV) - Mulubale, Sanny; Bwalya, Katongo; Mundando, Janet (Advances in Social Sciences Research Journal, 2022)
This article discusses HIV positive teachers’ medicalisation in the Zambian context. It makes a theoretical appraisal of the dynamics of health in this HIV treatment era, viewing the era as leaving the AIDS pandemic between two streams: a disappearing tragedy and a treatable illness with latent psychological, social and economic effects [1]. Teacher training, teachers’ economic status, their use of effective pedagogy and many other factors have been chronicled extensively by various scholars across disciplines in research on education in developing countries. However, teachers’ experiences of illness and health conditions, as key actors in implementing the development agenda of many countries in Africa, have received very limited attention. The HIV/AIDS burden in Sub-Saharan Africa (SSA) is higher than available resources to deal with the pandemic effectively [2] while the number of people living with the virus and on ART in SSA countries, such as Zambia, remains high [3]. The above proposition in this paper is supported by three fundamental concepts which can be surmised as: governmentality and identity. These two concepts – when effectively synthesised – offer new ways of understanding the medical solutions, normalcy, and their limits in the everyday living of teachers who are on ART. Based on this theoretical analysis and its relation to existing empirical data, the central argument in the paper is that teachers’ daily lives seem to be filled with the socio-political and economic consequences of HIV medicalisation and that these consequences seem to shape and limit how teachers manage and make sense of their acquired ‘therapeutic citizenship’ status.